Pemetaan lahan pertanian pangan berkelanjutan Di distrik aifat, aitinyo dan Ayamaru Utara Kabupaten Maybrat - Herman Tubur; M Sagrim; S Bachri; K Naa; M Howay (Fakultas Pertanian Universitas Papua, 2022)
Land is the main factor of agriculture development and food production, but along with the population increase, the pace of development, and the increase in the function of land for food also affect the availability of land to support national food security. The research was conducted in November–December 2020 in Maybrat Regency in 3 districts, North Ayamaru, Aifat and Aitinyo, to find out Characteristics of the slope of the land for the development of food crop agriculture, potential land as Sustainable Food Agricultural Land and Sustainable Food Agricultural Reserve Land and Mapping the physical aspects of land in the LP2B and LCP2B land areas. The results showed that the total land area in 3 observation districts with flat conditions (slope 0-8%) suitable for food crop development was 42,239 ha, with details of Aifat 23,166 ha, Aitinyo 13,731 ha, and North Ayamaru 5,341 ha. Based on the slope aspect, the potential area to be built and the availability of road infrastructure, there are 7,091 ha of potential land for sustainable food agriculture (LP2B) and 6,698 ha of sustainable food agriculture reserves (LP2B). Physical factors for the development of LP2B and LCP2B such as soil depth, drainage and commodities are in the appropriate category.